2004
DOI: 10.1093/jac/dkh481
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and molecular analysis of mef(A)-containing elements in tetracycline-susceptible and -resistant Streptococcus pyogenes clinical isolates with efflux-mediated erythromycin resistance

Abstract: The mef(A) gene is carried on different chromosomal genetic elements depending on whether the isolates are susceptible or resistant to tetracycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 25 publications
3
44
0
Order By: Relevance
“…The detection of the orf9 and orf56 genes of the 5Ј-and 3Ј-end regions of transposon Tn1207.3 in this mef(A)-containing strain indicated that Tn1207.1 was integrated into the conjugative transposon Tn1207.3. In addition, the detection of the tet(M) gene and not of tet(O) in this erythromycin-and tetracycline-resistant strain ruled out the carriage of Tn1207.1 into the recently described tet(O)-mef(A) element (7).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The detection of the orf9 and orf56 genes of the 5Ј-and 3Ј-end regions of transposon Tn1207.3 in this mef(A)-containing strain indicated that Tn1207.1 was integrated into the conjugative transposon Tn1207.3. In addition, the detection of the tet(M) gene and not of tet(O) in this erythromycin-and tetracycline-resistant strain ruled out the carriage of Tn1207.1 into the recently described tet(O)-mef(A) element (7).…”
Section: Discussionmentioning
confidence: 64%
“…In S. pneumoniae, mega can be inserted at different sites in the chromosome or into a transposon Tn916-like genetic element, forming a new composite named Tn2009, which also contains the tetracycline resistance tet(M) gene (12,26). Tn1207.1 has been found in S. pneumoniae inserted within the competence celB gene (11,28), and in S. pyogenes, Tn1207.1 has been described as integrated into the conjugative transposon Tn1207.3 and into a conjugative tet(O)-mef(A) element (4,7,9,26).…”
Section: Streptococcus Agalactiae (Lancefield Group B Streptococcus)mentioning
confidence: 99%
“…Y07780) (45) and of 98.5% with the same gene from S. pyogenes recently described in Italy (GenBank accession no. AJ715499) (4,14). No apparent linkage between mef(E) and tet(O) was detected in this strain in cross-PCR assays with primers specific for the two genes.…”
Section: Tet(l) Tet(m) and Tet(o)mentioning
confidence: 83%
“…The failure to find it in Europe had been attributed to the requirement for acquisition of the gene and the absence of selective pressure (18). However, the tet(O) gene has recently been found to be the customary tetracycline resistance determinant in the erythromycin-resistant S. pyogenes strains carrying gene mef(A) (4,14) or erm(A) (14).…”
Section: Tet(l) Tet(m) and Tet(o)mentioning
confidence: 99%
“…Lately, a third chimeric element containing mefA and tetO, a tetracycline resistance gene, was described as having both conjugative-transposon and bacteriophage characteristics (21). These tetO-mefA chimeric elements are different from the other two elements, as they are composed of a varying number of genes similar to those of Tn1207.1 that have combined with a different set of bacteriophage genes, resulting in elements of various sizes (52 to 60 kb), which are integrated into chromosomal locations outside of the comEC gene (9,21,22).…”
mentioning
confidence: 99%